NURSING AND CONSTRUCTIVISM: A NOVEL PEDIATRIC ICU NURSE ORIENTATION PROGRAM FOR NEWLY GRADUATED NURSES - Babb, William (Acta Scientiae et Intellectus, 2024)
The orientation process for newly graduated registered nurses (RNs) is extremely important as these RNs work to put theoretical learning into the practice of nursing care. During orientation, a new nurse begins what can be a harrowing process starting on a continuum that progresses from novice to competent nursing professional. Movement along this continuum can seem more distressing for new RNs in the pediatric critical care setting as the natures of both pediatric and critical care nursing are taken into consideration. The purpose of this paper is to detail the new graduate orientation efforts undertaken by a Southwestern United States Level One trauma center pediatric intensive care unit (PICU). Employing key elements from Benner’s Novice to Expert model, Fawcett’s metaparadigm components, and constructivist learning principles, this PICU has structured a 17-week new graduate nurse orientation program. This orientation program has succeeded in “building” and nurturing newly graduated RNs who can not only care for critically ill children, but who also have the nursing knowledge foundation to teach other new nurses.